Differential activation of Wnt-β-catenin pathway in triple negative breast cancer increases MMP7 in a PTEN dependent manner. - Nandini Dey (Public Library of Science (PLoS), 2013)
Mutations of genes in tumor cells of Triple Negative subset of Breast Cancer (TNBC) deregulate pathways of signal transduction. The loss of tumor suppressor gene PTEN is the most common first event associated with basal-like subtype (Martins, De, Almendro, Gonen, and Park, 2012). Here we report for the first time that the functional upregulation of secreted-MMP7, a transcriptional target of Wnt-β-catenin signature pathway in TNBC is associated to the loss of PTEN. We identified differential expression of mRNAs in several key-components genes, and transcriptional target genes of the Wnt-β-catenin pathway (WP), including beta-catenin, FZD7, DVL1, MMP7, c-MYC, BIRC5, CD44, PPARD, c-MET, and NOTCH1 in FFPE tumors samples from TNBC patients of two independent cohorts. A similar differential upregulation of mRNA/protein for beta-catenin, the functional readout of WP, and for MMP7, a transcriptional target gene of beta-catenin was observed in TNBC cell line models. Genetic or pharmacological attenuation of beta-catenin by SiRNA or WP modulators (XAV939 and sulindac sulfide) and pharmacological mimicking of PTEN following LY294002 treatment downregulated MMP7 levels as well as enzymatic function of the secreted MMP7 in MMP7 positive PTEN-null TNBC cells. Patient data revealed that MMP7 mRNA was high in only a subpopulation of TNBC, and this subpopulation was characterized by a concurrent low expression of PTEN mRNA. In cell lines, a high expression of casein-zymograph-positive MMP7 was distinguished by an absence of functional PTEN. A similar inverse relationship between MMP7 and PTEN mRNA levels was observed in the PAM50 data set (a correlation coefficient of -0.54). The PAM50 subtype and outcome data revealed that the high MMP7 group had low pCR (25%) and High Rd (74%) in clinical stage T3 pathologic response in contrast to the high pCR (40%) and low residual disease (RD) (60%) of the low MMP7 group.